Financiamento de ações no campo da saúde pública por meio de instrumentos de cooperação - Jesus, Elias Silva de (2017)
Purpose- The purpose of this study was to comprehend the challenges to be overcome by Fiocruz’ budgetary and financial management, due to the cooperation terms signed with the National Health Fund (NHF) being the main financing source of the institution’s final activities. It was found that the cooperation terms are signed between Fiocruz and the FNS because of the alignment of Fiocruz’strategic objectives, the demands from the National Health Service (NHS) and the public health policies proposed by the Ministry of Health. Design/Methodology- Adopting case study methodology, after documentation analysis, interviews and data analysis of the Strategic Management Supporting System (SMSS/Fiocruz), regarding the cooperation terms signed with the NHF from 2011 to 2015, from the evidences found, it was possible to stablish connections among them and to understand how these cooperation instruments execution process occurs in the institutional scope. Findings- It was found that the cooperation terms are signed between Fiocruz and the FNS because of the alignment of Fiocruz’strategic objectives, the demands from the National Health Service (NHS) and the public health policies proposed by the Ministry of Health. The importance of Fiotec, Fiocruz’ supporting foudation, was also highlighted on operating the cooperation terms signed with the NHF, showing the need for harmonization and interaction between Fiocruz and Fiotec, for a better process management as a whole. Research limitations- The main limitation of the research was the impossibility of analyzing in a deeper way, as it would be desirable, the operationalization of the terms of cooperation originating from the FNS within Fiotec. However, in the propositions suggested based on the inferences made from the evidence, it is proposed the adjustment of the Fiocruz / Fiotec relationship as well as the harmonization of the processes between the foundations. Practical implications- After comprehending the challenges of Fiocruz’ budgetary and financial management in operating these cooperation terms and understanding the behavior of these cooperation instruments in the execution process, the study proposed actions that may contribute with this initiative in many aspects. Social implications- By understanding the phenomenon elucidated on this study, it has become clear the institutional need of advancing on management improvement of the cooperation terms signed with the NHF, so that Fiocruz can be more efficient and effective in implementing its strategic objectives financed through these cooperation instruments. Originality- To our knowledge, this is the first study related to the behavior of cooperation instruments with source of funding for public institutions to take action in the field of public health